Birth cohort-specific smoking patterns in Japan (1906–2004): a population-based study from the NC-CCAPH consortiumResearch in context - Shiori Tanaka; Hikaru Ihira; Tetsuya Tajima; Rieko Kanehara; Yosuke Inoue; Takehiko Doi; Nozomu Kobayashi; Yuka Kato; Yukiko Nishita; Maki Konishi; Yoko M. Nakao; Isamu Kabe; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: This study aimed to estimate Japan’s age-specific history of smoking prevalence, initiation, cessation, and intensity by birth cohort, using data from multiple cohort studies. Methods: We pooled data from eight eligible cohorts surveyed between 1989 and 2020 as part of the National Center Cohort Collaborative for Advancing Population Health (NC-CCAPH). An Age-Period-Cohort model was employed to estimate birth cohort- and sex-specific smoking patterns for individuals born between 1920 and 1999. Findings: Among 393,023 participants (40.9% female, mean age 51.8 years), smoking prevalence peaked in early adulthood (20s–30s) and declined with increasing age. Recent birth cohorts showed lower prevalence and smoking initiation in both sexes, albeit with increases in mid-female cohorts (1960s–1980s). Smoking cessation surged in the late 1990s and peaked around 2010, coinciding with tax-driven cigarette price hikes. Peak cigarette consumption occurred in 1990, followed by a steady decline. However, all birth cohorts maintained a mean consumption above 10 cigarettes smoked per day for both sexes. Interpretation: This study highlights a generational shift in smoking behavior, in which younger birth cohorts smoked less and quit earlier than older birth cohorts. The study also reveals that smoking behaviors in males were strongly influenced by cigarette accessibility, such as price increases, while smoking initiation in females was more likely affected by societal changes, especially in the evolving roles of women. Smoking intensity remained stable across cohorts and sexes, emphasizing the need for stronger health policies, including higher tobacco taxes, to further reduce smoking and its health impact. Funding: This study was conducted within the National Center Cohort Collaborative for Advancing Population Health (NC-CCAPH) and supported by grants from the Japan Health Research Promotion Bureau (JH) (2019-(1)-1, 2024-B-05).